Pengembangan Media Pembelajaran Game PEKA Untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Pada Materi Pecahan - Putri, Alfa Reza Silvia; Airlanda, Gamaliel Septian (Efektor, 2020)
Based on the results of observations, there are problems with elementary school students, namely not maximum learning outcomes in the mathematical fraction count operations material. The purpose of this research and development is to develop the PEKA game media (Mathematical Fraction) that can be used as a learning media for fractions to improve learning outcomes. The PEKA game media was created to facilitate the delivery of material and student's understanding of fractions. In this research and development, the writer uses the model developed by Borg & Gall. The steps used in this research and development are (1) Research and development of initial information, (2) Planning, (3) Development of initial product drafts, (4) Initial trials, (5) Product revision. The results showed that the PEKA game media scored very well. The average score obtained from material experts is 84% ​​with very good assessment criteria, and the average score obtained from media experts is 92% with very good assessment criteria.